Advanced software for MRgFUS treatment planning - Filippou, Antria; Georgiou, Andreas; Nikolaou, Anastasia; Evripidou, Nikolas; Damianou, Christakis A. (My University, 2023)
Herein, a user-friendly software platform for 3-dimensional Focused Ultrasound treatment planning based on Magnetic Resonance Imaging (MRI) images is presented.
Keywords: HIFU; MRgFUS; Software; Treatment planning